2010
DOI: 10.1016/j.ijproman.2009.11.009
|View full text |Cite
|
Sign up to set email alerts
|

A review of studies on Public–Private Partnership projects in the construction industry

Abstract: Public Private Partnership (PPP) in construction is gaining in popularity. Although papers published in major journals have documented real cases of PPP projects, there appears to be a lack of systematically summarizing what they have already provided.Consequently, this paper reviewed PPP studies published in the six top journals in the This is the Pre-Published Version.2 construction field. The objectives are to compare and contrast the findings of the studies so as to provide insights for directing further P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
235
0
17

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 351 publications
(297 citation statements)
references
References 112 publications
8
235
0
17
Order By: Relevance
“…(Ke et al, 2009;Tang et al, 2010), while the research interests of PPP in China on strategies and framework in choosing the right type of PPP, financing structure optimization, legal issues, concession period design and pricing mechanism (Shan and Ye, 2012).Regarding some of the topics, there are several review publications to summarize the PPP application in China in order to draw lessons for future references. For instances, Ke et al (2014) summarized the application of PPP in China in terms of opportunities, environment and usage; Wang et al (2014) analyzed the overall application of PPP by examining the characteristics and classical projects in different sectors; Adams et al (2006) examined the PPP system and major models in China and identified the key constraints; Mu et al (2011) analyzed and explained the institutional transition process of PPP in China's transportation based on the Path Dependence Theory; reviewed and assessed the development of PPP in China's urban water sector based on a self-collected project database on 152 water supply projects and 200 waste water treatment projects.…”
Section: Introductionmentioning
confidence: 99%
“…(Ke et al, 2009;Tang et al, 2010), while the research interests of PPP in China on strategies and framework in choosing the right type of PPP, financing structure optimization, legal issues, concession period design and pricing mechanism (Shan and Ye, 2012).Regarding some of the topics, there are several review publications to summarize the PPP application in China in order to draw lessons for future references. For instances, Ke et al (2014) summarized the application of PPP in China in terms of opportunities, environment and usage; Wang et al (2014) analyzed the overall application of PPP by examining the characteristics and classical projects in different sectors; Adams et al (2006) examined the PPP system and major models in China and identified the key constraints; Mu et al (2011) analyzed and explained the institutional transition process of PPP in China's transportation based on the Path Dependence Theory; reviewed and assessed the development of PPP in China's urban water sector based on a self-collected project database on 152 water supply projects and 200 waste water treatment projects.…”
Section: Introductionmentioning
confidence: 99%
“…In 80s of last century, in the overall privatization ideas, the British government began to advocate PPP mode. The British government is a pioneer advocate of PPP, and it is also the promoters of PPP [1]. PPP is the abbreviation of three English words which include private, partnership, and public.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, there are also variable schemes, differing in efficiency [2]. All these speak for the urgency of the research, the practical importance of attracting money to the fund renewal, and the need for the innovative approach for the solution of the problems, existing in the field [18].…”
Section: Introductionmentioning
confidence: 99%